2003
DOI: 10.1023/b:rubi.0000008894.80972.2e
|View full text |Cite
|
Sign up to set email alerts
|

A Catecholic Siderophore Produced by the Thermoresistant Bacillus licheniformis VK21 Strain

Abstract: Thermophilic and thermoresistant strains of bacilli were screened on a medium containing Chrome Azurol S for producers of siderophores. It was found that the Bacillus licheniformis VK21 strain dramatically increases secretion of the metabolite, a chelator of Fe3+, in response to addition of manganese(II) salts. The growth of the producer on a minimum medium containing MnSO4 under the conditions of iron deficiency is accompanied by the accumulation of a catechol product, the content of which reaches a maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Fe-binding chelators, known as siderophores, bind or capture free Fe (III) and transport iron into the cell (Neilands and Nakamura 1991). Many different types of siderophores have been studied and identified in different bacterial genera including Bacillus (Park et al 2005;Temirov et al 2003;Wilson et al 2006). The relation between siderophore production, plant growth promotion, and uptake of Fe has also been well documented for a variety of plants and microorganisms.…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 99%
“…Fe-binding chelators, known as siderophores, bind or capture free Fe (III) and transport iron into the cell (Neilands and Nakamura 1991). Many different types of siderophores have been studied and identified in different bacterial genera including Bacillus (Park et al 2005;Temirov et al 2003;Wilson et al 2006). The relation between siderophore production, plant growth promotion, and uptake of Fe has also been well documented for a variety of plants and microorganisms.…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 99%
“…Thus, it seems extremely likely that the extracellular, riboflavinlike compound released into solution by the alkaliphilic iron-reducing community during growth was acting as an electron-shuttling compound and had a role in Fe(III) reduction; this is the first time that this has been shown to occur at alkaline pH. Given that even mesophilic bacteria can adopt a wide variety of mechanisms to perform similar physiological functions when interacting with their environment (74) and the stress of a challenging environment has led extremophilic bacteria to evolve distinctly different mechanisms in many cases (45,75), it is striking that the electronshuttling compound found in this study of alkaliphiles is indistinguishable from that used by mesophiles. Interestingly, flavins have also been found in the culture supernatants of several methanotrophic species (36), indicating that this method of extracellular electron transfer may be more widespread among anaerobic communities living on the brink of life than first thought.…”
Section: Discussionmentioning
confidence: 99%
“…Temirov et al (32) reported that the addition of manganese(II) salts to growth medium dramatically increased the secretion of a catecholic (Fe 3ϩ ) siderophore by Bacillus licheniformis strain VK21. The chrome azurol S (CAS) assay, a common diagnostic test for siderophore production (26), was used to determine if an iron-chelating metabolite was produced in liquid culture medium.…”
mentioning
confidence: 99%
“…In the genus Bacillus, Bacillus megaterium and Bacillus subtilis are producers of schizokinen and bacillibactin, respectively (6,20). Bacillus anthracis produces both a catechol and a hydroxamate siderophore (7,34), and B. licheniformis strain VK21 is the only known example of a thermoresistant catecholate-producing Gram-positive bacterium (32).…”
mentioning
confidence: 99%